Administrative sanctioning law in Spanish legislation of transparency and good governance: significant aspects - Ochoa Monzó, Josep (2020)
This paper analyzes the penalty system within the Spanish transparency and good governance legal framework as following Law 19/2013, of December 9th, on transparency, access to public information and good governance (LTBG), which is a framework law in this matter for the whole Spanish State to avoid bad practices and corruption. This paper will also tackle the derivations that Spanish Autonomous Communities have introduced through their own regulations. Through this analysis I intend to prove that this matter, despite outstanding singularities, encompasses the principles and rules of the general penalty power of the Public Administration and the Penalty Administrative Law. This study also aims to reflect said reality and draw a comparison with the Peruvian legal framework.